A checklist of scale insects of Slovenia - Seljak, Gabrijel (ENTOMOLOGIA HELLENICA, 2010)
The last list of scale insects of Slovenia was compiled by Franc Janežič (1954) and included 44 species. On the basis of data gathered from the literature and from our own faunistic researches, a new list of scale insects recorded from or found in the territory of Slovenia is presented. Altogether 101 species from 9 families are listed here: Ortheziidae (1 species), Margarodidae (1 species), Pseudococcidae (18 species), Eriococcidae (8 species), Asterolecaniidae (2 species), Coccidae (26 species), Kermesidae (1 species), Cerococcidae (1 species) and Diaspididae (43 species). Eighteen are new to the fauna of Slovenia.